A-ZIP53, a dominant negative reveals the molecular mechanism of heterodimerization between bZIP53, bZIP10 and bZIP25 involved in Arabidopsis seed maturation. Issue 1 (December 2017) - Jain, Prateek; Shah, Koushik; Sharma, Nishtha; Kaur, Raminder; Singh, Jagdeep; Vinson, Charles; Rishi, Vikas
Abstract InArabidopsis, maturation phase, an intricate process in seed formation is tightly regulated by the DNA binding activity of protagonist basic leucine zipper 53 (bZIP53) transcription factor and its heterodimerizing partners, bZIP10 and bZIP25. Structural determinants responsible for heterodimerization specificity of bZIP53 are poorly understood. Analysis of amino acid sequences of three bZIPs does not identify interactions that may favor heterodimerization. Here, we describe a designed dominant negative termed A-ZIP53 that has a glutamic acid-rich amphipathic peptide sequence attached to N-terminal of bZIP53 leucine zipper. Circular dichroism (CD) and mass spectrometry studies with equimolar mixture of three bZIP proteins in pairs showed no heterodimer formation whereas A-ZIP53 interacted and formed stable heterodimers with bZIP53, bZIP10, and bZIP25. A-ZIP53 electrostatically mimics DNA and can overcome repulsion between basic DNA binding regions of three bZIP proteins. Gel shift experiments showed that A-ZIP53 can inhibit the DNA binding of three proteins. CD studies demonstrated the specificity of A-ZIP53 as it did not interact with bZIP39 and bZIP72. Transient co-transfections inArabidopsis protoplasts showed that A-ZIP53 inhibited three bZIPs and their putative heterodimers-mediated transactivation of GUS reporter gene. Furthermore, four newly designed acidic extensions were evaluated for their ability to interact with three bZIPs.